2015
DOI: 10.5194/acp-15-1573-2015
|View full text |Cite
|
Sign up to set email alerts
|

Carbonaceous aerosols on the south edge of the Tibetan Plateau: concentrations, seasonality and sources

Abstract: Abstract. To quantitatively evaluate the effect of carbonaceous aerosols on the south edge of the Tibetan Plateau, aerosol samples were collected weekly from August 2009 to July 2010 at Qomolangma (Mt. Everest) Station for Atmospheric and Environmental Observation and Research (QOMS, 28.36° N, 86.95° E, 4276 m a.s.l.). The average concentrations of organic carbon (OC), elemental carbon (EC) and water-soluble organic carbon were 1.43, 0.25 and 0.77 μg m−3, respectively. The concentration levels of OC and EC at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
162
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(192 citation statements)
references
References 57 publications
27
162
3
Order By: Relevance
“…The average ratios for Regions I, II, and III were 1.82, 1.31, and 1.14, respectively (Table 2), indicating a decreasing impact of biomasssourced aerosol deposition in snow over the TP. The slightly higher OC / BC in Region I may be due to its proximity to South Asian combustion sources dominated by biomass burning (Cong et al, 2015a, b;Li et al, 2016). For example, in the LHG region, lower LAP concentrations in fresh clean snow were observed at LHG3 and LHG6 (Fig.…”
Section: Distributions Of Lapsmentioning
confidence: 95%
See 1 more Smart Citation
“…The average ratios for Regions I, II, and III were 1.82, 1.31, and 1.14, respectively (Table 2), indicating a decreasing impact of biomasssourced aerosol deposition in snow over the TP. The slightly higher OC / BC in Region I may be due to its proximity to South Asian combustion sources dominated by biomass burning (Cong et al, 2015a, b;Li et al, 2016). For example, in the LHG region, lower LAP concentrations in fresh clean snow were observed at LHG3 and LHG6 (Fig.…”
Section: Distributions Of Lapsmentioning
confidence: 95%
“…Ratios of OC to BC (OC / BC) were used to examine the possible impact of biomass burning in previous studies (Watson et al, 2001;Bond et al, 2013;Cong et al, 2015a, b). Usually, the aerosols emitted from biomass burning have higher OC / BC ratios than that from fossil fuel combustion.…”
Section: Distributions Of Lapsmentioning
confidence: 99%
“…The so-called "Atmospheric Brown Cloud (ABC)", a 3 kmthick brownish layer of pollutants, has been detected extending from the Indian Ocean to the Himalayas (Tripathi et al, 2005;Ramanathan et al, 2007). The aerosols that gather in the foothills can be lifted to high altitudes Qiu, 2013) and can even travel across the high Himalayas and reach the Tibetan Plateau (TP) (Bonasoni, 2008;Xia et al, 2011;Chen et al, 2015a;Cong et al, 2015;Lüthi et al, 2015), thus affecting the atmospheric quality and causing environmental risks in the high and remote regions.…”
Section: Introductionmentioning
confidence: 99%
“…1.4 µg m −3 at Qomolangma, Mt Everest, 4276 m a.s.l., by Cong et al, 2015 and 4 µg m −3 at the NW Pacific, 2-6.5 km column by Heald et al, 2005). FT-PM T OC under SAL conditions (0.77 µg m −3 ) was higher than under WES (0.52 µg m −3 , including the BBE) events.…”
Section: Fraction Determined Of Ommentioning
confidence: 96%
“…Succinic (suc) and phthalic (pth) acids were the most abundant dicarboxylic acids (Table 2) with FT and BL average values (suc: 6.5-3.7; pth: 3.2-2.8 ng m −3 for the FT-BL) much lower than those found for PM 2.5 in the FT Mount Tai (suc: 30 ng m −3 ; Wang et al, 2009), similar to those observed in PM T in the Himalayas (4276 m a.s.l.) (suc: 13.7; pth: 9.5 ng m −3 ; Cong et al, 2015), but higher than those detected in the North Pacific for remote marine PM T (suc: 2.8; pth: 0.66 ng m −3 ; Kawamura and Sakaguchi, 1999). Malic acid within the BL (the third most abundant polyacid at Izaña; Table 2) might be photochemical in origin via OH oxidation of the surrounding biogenic compounds transported by the daytime upslope winds.…”
Section: Dicarboxylic Acidsmentioning
confidence: 99%